Intra‐individual stability of longitudinal urinary steroid profiles in Swedish athletes - Ekström, Lena; Mous, Dinah; Heiland, Vincent; Heiland, Emerald G.; Schulze, Jenny (Drug testing and analysis, 2023)
The steroid module of the athlete biological passport (ABP) aims to detect doping with endogenous steroids by longitudinally monitoring epitestosterone (E), testosterone (T), and four metabolically related steroids and their ratios. There are large variations in the urinary levels of the androgen metabolites due to genetic polymorphisms, drug use, menstrual cycle, and other factors. In this study, we aimed to increase our understanding of the natural, within‐individual variations of the established ABP markers in males and females over time, looking at samples collected both in and out‐of‐competition (IC/OOC). Urinary steroid profiles from 323 Swedish athletes, with at least five samples per athlete, were extracted from ADAMS together with information on type of sport, IC/OOC, and time of day. Data were analyzed using coefficient of variation (CV%) to examine within‐subject variability and linear mixed effects models to estimate within‐subject change in the metabolites over time. The metabolites and ratios expressed higher individual CV% in females (23–56) than in males (18–39). Samples taken OOC showed larger intra‐individual variations than samples collected IC for most of the ABP metabolites in both sexes. The median concentrations were higher IC for some metabolites, particularly testosterone being 52% higher among females. Time of day influenced the intra‐individual variation of the urinary steroid profile with decreases in androgen metabolites over time, if measured in evening versus daytime. These findings can aid in the testing strategies and interpretation of the steroidal module of ABP. The levels of urinary athlete biological passport (ABP) steroids and ratios were influenced by gender, time point of collection, and if samples were taking in or out of competition. One notably finding was that testosterone levels were 50% higher in samples taken in competition than out of competition among female athletes, whereas minor difference in males.